Dissection of the multichannel reaction of acetylene with atomic oxygen: from the global potential energy surface to rate coefficients and branching dynamics. Issue 3 (2nd January 2019) - Zuo, Junxiang; Chen, Qixin; Hu, Xixi; Guo, Hua; Xie, Daiqian
Abstract : A global potential energy surface for the O( 3 P) + C2 H2 reaction is developed and the quasi-classical trajectory study on the potential energy surface reproduce the rate coefficient and product branching ratio. Abstract : The O( 3 P) + C2 H2 reaction is the first step in acetylene oxidation. The accurate kinetic data and the understanding of the reaction dynamics is of great importance. To this end, a full-dimensional global potential energy surface (PES) for the ground triplet state of the O( 3 P) + C2 H2 reaction is constructed based on approximately 85 000 ab initio points calculated at the level of explicitly correlated unrestricted coupled cluster single, double, and perturbative triple excitations with the explicitly correlated polarized valence triple zeta basis set (UCCSD(T)-F12b/VTZ-F12). The PES is fit using the permutation invariant polynomial-neural network (PIP-NN) approach with a total root mean square error of 0.21 kcal mol −1 . The key topographic features of the PES, including multiple potential wells and saddle points along different reaction pathways, are well represented by this fit PES. The kinetics and dynamics of the O( 3 P) + C2 H2 reaction are investigated using the quasi-classical trajectory (QCT) method. The calculated rate coefficients are in good agreement with experimental data over a wide temperature range, especially when the temperature is lower than 1500 K. The product branch ratio has also been determined, which indicates the H + HCCO channel as the dominant reaction pathway at 298–3000 K, accounting for 80–90% of the overall rate coefficient, in agreement with experimental observations. The dynamics of the reaction is analyzed in detail.